Using nanoscopy to probe the biological activity of antimicrobial leads that display potent activity against pathogenic, multidrug resistant, gram-negative bacteria. - Smitten,KL; Southam,HM; Bernardino,de la Serna J; Gill,MR; Jarman,PJ; Smythe,CGW; Poole,RK; Thomas,JA (ACS Nano, 2019)
Medicinal leads that are also compatible with imaging technologies are attractive, as they facilitate the development of therapeutics through direct mechanistic observations at the molecular level. In this context, the uptake and antimicrobial activities of several luminescent dinuclear RuII complexes against E. coli were assessed and compared to results obtained for another ESKAPE pathogen, the Gram-positive major opportunistic pathogen Enterococcus faecalis, V583. The most promising lead displays potent activity, particularly against the Gram-negative bacteria, and potency is retained in the uropathogenic multidrug resistant EC958 ST131 strain. Exploiting the inherent luminescent properties of this complex, super-resolution STED nanoscopy was used to image its initial localization at/in cellular membranes and its subsequent transfer to the cell poles. Membrane damage assays confirm that the complex disrupts the bacterial membrane structure before internalization. Mammalian cell culture and animal model studies indicate that the complex is not toxic to eukaryotes, even at concentrations that are several orders of magnitude higher than its minimum inhibitory concentration (MIC). Taken together, these results have identified a lead molecular architecture for hard-to-treat, multiresistant, Gram-negative bacteria, which displays activities that are already comparable to optimized natural product-based leads.